2010
DOI: 10.1002/ca.20960
|View full text |Cite
|
Sign up to set email alerts
|

The contribution of the palmaris longus muscle to the strength of thumb abduction

Abstract: The palmaris longus muscle (PLM) is described as a weak flexor of the wrist and a tensor of the palmar aponeurosis, but not a thumb abductor. The PLM is believed to aid thumb abduction through its insertion onto the thenar eminence. Two groups, both right hand dominant, were selected from 1,200 sampled participants. The first group comprised of 38 subjects with unilateral presence of the PLM and was used to determine the strength of thumb abduction. The second group comprised of 30 subjects, with bilateral pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
17
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 17 publications
3
17
0
Order By: Relevance
“…It also opposes strong shearing forces on the skin of the palm during gripping, aiding in cupping of the hand (Snell, ). In most cases, the distal tendon has a lateral slip that attaches to the superficial surface of the abductor pollicis brevis that may contribute to thumb abduction (Gangata et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…It also opposes strong shearing forces on the skin of the palm during gripping, aiding in cupping of the hand (Snell, ). In most cases, the distal tendon has a lateral slip that attaches to the superficial surface of the abductor pollicis brevis that may contribute to thumb abduction (Gangata et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Several exams have been described which test for the PL, the standard being Schaeffer's test in which the patient joins the thumb to little finger while flexing the wrist [3]. It has been suggested that the palmaris longus contributes to the strength of thumb abduction and may provide an advantage to sports that require hand grip [4, 5]; however, most studies have shown that absence of the PL is not associated with any significant physical or functional deficits, and therefore, the PL is frequently harvested for use in many different hand, reconstructive, and orthopedic surgeries [3, 6–10]. The PL has a characteristically short belly and long tendon, making it an ideal donor for tendon grafts for secondary tendon reconstruction, tendon transfers, and other reconstructive efforts [11].…”
Section: Introductionmentioning
confidence: 99%
“…The muscle is often used by hand surgeons as a tendon graft and has been used to reconstruct ligaments and tendons. The Palmaris longus is a weak flexor of the wrist joint and also tenses the palmar fascia[4].Though the rate of absence of the Palmaris Longus has been documented in many African populations, this has not been documented in East Africa by clinical methods in a large population[5], [6]. The Palmaris longus is also of interest because of the association with clinical conditions of the hand, genetics and anthropology [5], [7].…”
Section: Introductionmentioning
confidence: 99%